2015
DOI: 10.1002/hed.24113
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of lymph node density in squamous cell carcinoma of the tongue

Abstract: Our data suggest that lymph node density is a reliable and applicable predictor of prognosis in patients with tongue SCC. © 2015 Wiley Periodicals, Inc. Head Neck 38: E859-E866, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 36 publications
(127 reference statements)
1
70
0
Order By: Relevance
“…Our results agree with those showing that LND and nodal extracapsular spread were clinically significant in patients with head and neck cancer. [10][11][12]16,17 To our knowledge, most published studies have been in oral cavity cancers. LND may have greater prognostic value than the absolute number of positive lymph nodes, as the former involves two factors, the number of positive lymph nodes and the extent of surgical treatment (number of lymph nodes removed).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results agree with those showing that LND and nodal extracapsular spread were clinically significant in patients with head and neck cancer. [10][11][12]16,17 To our knowledge, most published studies have been in oral cavity cancers. LND may have greater prognostic value than the absolute number of positive lymph nodes, as the former involves two factors, the number of positive lymph nodes and the extent of surgical treatment (number of lymph nodes removed).…”
Section: Discussionmentioning
confidence: 97%
“…[7][8][9] In head and neck cancer, retrospective studies have suggested that the LND may be prognostic in oral cavity squamous cell carcinoma. [10][11][12] This parameter incorporates not only the burden of nodal disease and cancer spread but also the extent of nodal dissection and surgical staging. To our knowledge, no study to date has assessed the prognostic significance of LND in stratifying the risks of cancer-specific survival in patients with HPSCC after surgery in a single institution.…”
mentioning
confidence: 99%
“…To optimize treatment and management of these patients, markers are needed that predict the risk of locoregional recurrence. Currently, TNM‐based staging, perineural invasion, lymphovascular invasion, extracapsular spread, and resection margin status are routinely used in risk stratification of locoregional recurrence . In recent years, multiple studies focused on the influence of lymph node ratio on the prognosis of patients with oral SCC and suggested the lymph node ratio as a very promising marker for locoregional recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, TNM‐based staging, perineural invasion, lymphovascular invasion, extracapsular spread, and resection margin status are routinely used in risk stratification of locoregional recurrence . In recent years, multiple studies focused on the influence of lymph node ratio on the prognosis of patients with oral SCC and suggested the lymph node ratio as a very promising marker for locoregional recurrence . In 2013, Patel et al concluded from their multi‐institutional study, conducted on 4254 patients, that the lymph node ratio is a strong independent prognostic marker for patients with oral SCC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation